Visual Subcultures and City Intervention. Santiago, Chile, 1987-1983 - Munsell, Elizabeth (Universidad de Chile. Instituto de la Comunicación e Imagen, 2009)
A resistance discourse parts from an emergent visuality during the eighties in Chile, when a gradually more visual and mediatized cultural is fostered by the military government as an ideological apparatus of neoliberal capitalism. In response, subcultural youth dismantled the dominant culture's visual representations using non-mass-mediatized visual communications mediums. The subculturas that resulted from an increased contact with foreign countries did not passively assume the imported pop culture, but rather developed their critiques of the dominant visual culture and the military government through their distinct visuality, disseminating their cultural practices y alterable identities in Santiago's public space of high connectivity.